2016
DOI: 10.1021/acs.jpcc.5b10025
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Absorption within Single-Walled Carbon Nanotube Systems

Abstract: We study the photoabsorption properties of photoactive bulk polymer/fullerene/nanotube heterojunctions in the near-infrared region. By combining pump–probe spectroscopy and linear response time-dependent density functional theory within the random phase approximation (TDDFT-RPA) we elucidate the excited state dynamics of the E11 transition within (6,5) and (7,5) single-walled carbon nanotubes (SWNTs) and combined with poly(3-hexylthiophene-2,5-diyl) (P3HT) and [6,6]-phenyl-C61-butyric aci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Several studies on blends of conjugated polymers and SWCNT suggest that efficient exciton quenching occurs at these interfaces and many studies have shown direct evidence for the generation of mobile carriers in polymer-SWCNT composites. [21][22][23][24] After exciton dissociation, ballistic carrier transport in single tubes and extremely high conductivity in networks suggest that SWCNT may yield higher mobilities and form more conductive percolation networks than fullerenes. OPV cells based on CNTs as acceptor on the concept of BHJ is one of the most promising.…”
mentioning
confidence: 99%
“…Several studies on blends of conjugated polymers and SWCNT suggest that efficient exciton quenching occurs at these interfaces and many studies have shown direct evidence for the generation of mobile carriers in polymer-SWCNT composites. [21][22][23][24] After exciton dissociation, ballistic carrier transport in single tubes and extremely high conductivity in networks suggest that SWCNT may yield higher mobilities and form more conductive percolation networks than fullerenes. OPV cells based on CNTs as acceptor on the concept of BHJ is one of the most promising.…”
mentioning
confidence: 99%
“…We measured T/T dynamics on a spin-coated sample of semiconducting single-walled carbon nanotubes (SWNTs) starting from a highly concentrated dispersion in orthodichlorobenzene [20]. The resulting sample presents a large number of bundles and aggregates, with a predominance of the (6,5) and the (7,5) chiralities, resulting in a broad absorption band of the first excitonic transition (S11) centered at 1060 nm.…”
mentioning
confidence: 99%
“…We included two thirds of the number of electrons ( 2 ⁄3N e ) many bands within the calculations. This has been shown to be sufficient to converge the first π → π * transitions of graphene 46 and SWNT/polymer hybrid systems, 47 and the optical spectra of polymers and oligomers 48 in the random phase approximation (RPA). Structural optimization was performed within the atomic simulation environment (ASE), 49 until a maximum force below 0.05 eV/Å was obtained.…”
Section: Methodsmentioning
confidence: 99%